Description of immature stages and redescription of adults of Monocrepidius fuscofasciatus (Eschscholtz, 1829) (Elateridae, Agrypninae, Oophorini) - Marinho, Thaynara A.s.; Casari, Sonia A.; Prosvirov, Alexander S.; Rosa, Simone Policena (Zootaxa, 2023)
Monocrepidius Eschscholtz, 1829, previously Conoderus Eschscholtz, 1829, is one of the largest genera in Elateridae, with about 380 species distributed worldwide, with the majority of diversity in Australian and Neotropical regions. Several species groups have been recognized in Monocrepidius. Monocrepidius fuscofasciatus (Eschscholtz 1829) belongs to Candèze’s section I with seven species distributed in South America, predominantly in Brazil. Larvae of M. fuscofasciatus is undescribed and distribution of this species is poorly known. In the present work we describe mature larva, pupa and redescribe adults of M. fuscofasciatus, and also add information about distribution of this species. Monocrepidius fuscofasciatus larva is similar to that of M. malleatus Germar, 1824, its closest species with known larva. They differ from other American species in the presence of penicillus on mandible and abdominal tergum IX more setose, with a lateral row of 6 or 7 setae. In the other species, the penicillus is absent and the lateral row bears 2 or 3 setae. These results corroborate that larval evidence is useful in the taxonomy of this genus.